Data from: Genetic population structure and variation at phenology-related loci in anadromous Arctic char (Salvelinus alpinus) ... - Madsen, Rikke P.A.; Jacobsen, Magnus W.; O'Malley, Kathlee G.; Nygaard, Rasmus; Præbel, Kim; Jónsson, Bjarni; Pujolar, Jose M.; Fraser, Dylan J.; Bernatchez, Louis; Hansen, Michael M. (Dryad, 2020)
The Arctic will be especially affected by climate change, resulting in altered seasonal timing. Anadromous Arctic char (Salvelinus alpinus) is strongly influenced by sea surface temperature (SST) delimiting time periods available for foraging in the sea. Recent studies of salmonid species have shown variation at phenology-related loci associated with timing of migration and spawning. We contrasted genetic population structure at 53 SNPs versus four phenology-related loci among 15 anadromous Arctic char populations from Western Greenland and three outgroup populations. Among anadromous populations, the time period available for foraging at sea (> 2oC) ranges from a few weeks to several months, motivating two research questions: 1) Is population structure compatible with possibilities for evolutionary rescue of anadromous populations during climate change? 2) Does selection associated with latitude or SST regimes act on phenology-related loci? In Western Greenland, strong isolation-by-distance at SNPs was ... : SNP genotypes of Arctic charSNP genotypes (53 loci) encompassing all analyzed Arctic char populations in GENEPOP format.SNPs_all.genPhenology-related lociGenotypes at 4 phenology-related loci in all analyzed Arctic char populations in GENEPOP format.phenology-related_loci.gen ...